PERLINDUNGAN HUKUM PASIEN DI RUMAH SAKIT UMUM DARI PELAYANAN MEDIS - Nur Rohimah (Journal of Law and Justice, 2025)
This research also aims to understand hospital initiatives to overcome these problems. This study offers theoretical advantages by advancing the development of civil law and supplementing data for related studies in the fields of health care, medicine, and consumer protection. This research is qualitative legal research with an empirical juridical approach by collecting primary data obtained through observation and interviews. Secondary data was obtained through documentation. The data that has been collected is then reduced and analyzed using qualitative descriptive analysis. The results of this research show that the legal protection provided to patients is preventive protection, that is, before carrying out medical services, the hospital will first provide information to the patient regarding the existing rules at the hospital, as well as the risks that will occur. The problems that occur at the regional general hospital (RSUD), mostly occur because the services provided by the hospital are unsatisfactory, starting from unclear information and so on. Efforts made by the regional general hospital (RSUD) is to prioritize consumer (patient) rights by providing good service, paying attention to the performance of nurses and doctors in providing medical services to patients.